2021
DOI: 10.3389/feart.2021.620813
|View full text |Cite
|
Sign up to set email alerts
|

Local Explosion Detection and Infrasound Localization by Reverse Time Migration Using 3-D Finite-Difference Wave Propagation

Abstract: Infrasound data are routinely used to detect and locate volcanic and other explosions, using both arrays and single sensor networks. However, at local distances (<15 km) topography often complicates acoustic propagation, resulting in inaccurate acoustic travel times leading to biased source locations when assuming straight-line propagation. Here we present a new method, termed Reverse Time Migration-Finite-Difference Time Domain (RTM-FDTD), that integrates numerical modeling into the standard RTM back-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 35 publications
1
19
0
Order By: Relevance
“…Variations on the RTM method include back projection, stacking, source scanning, and time-reversal (e.g., Walker et al 2011;De Angelis et al 2012;Jolly et al 2014;Sanderson et al 2020). This approach is originally used to locate seismic (Ishii et al 2005;Kiser and Ishii 2011) and acoustic (Jolly et al 2014;Sanderson et al 2020;Fee et al 2021) sources related to volcanic eruptions, while here we identified the dominant propagation velocity across a seismic network. For the Ambae eruptions, the dominant frequency band of acoustic waves significantly differs from that of seismic tremor (Fig.…”
Section: Methods To Check For Air-to-ground-coupled Waves In Seismogramsmentioning
confidence: 99%
“…Variations on the RTM method include back projection, stacking, source scanning, and time-reversal (e.g., Walker et al 2011;De Angelis et al 2012;Jolly et al 2014;Sanderson et al 2020). This approach is originally used to locate seismic (Ishii et al 2005;Kiser and Ishii 2011) and acoustic (Jolly et al 2014;Sanderson et al 2020;Fee et al 2021) sources related to volcanic eruptions, while here we identified the dominant propagation velocity across a seismic network. For the Ambae eruptions, the dominant frequency band of acoustic waves significantly differs from that of seismic tremor (Fig.…”
Section: Methods To Check For Air-to-ground-coupled Waves In Seismogramsmentioning
confidence: 99%
“…Unlike ground-or satellite-based optical sensing, infrasound recording is not impacted by poor visibility, and data latency for local installations is usually less than a few tens of seconds. In its most basic application, infrasound can be used to detect and locate explosions (e.g., Matoza et al 2011Matoza et al , 2017De Angelis et al 2012), while more advanced data processing can characterize diverse eruptive activity (Anderson et al 2018a), discriminate between closely spaced vents (Ripepe et al 2007;Fee et al 2021), help forecast eruptions (Garcés et al 1999;Ulivieri et al 2013;Johnson et al 2018;Ripepe et al 2018), and provide quantitative eruption source parameters (e.g., Vergniolle & Caplan-Auerbach 2006;Ripepe et al 2013;). Near-real-time eruption monitoring with infrasound has been useful at well-monitored volcanoes, including at Tungurahua (Fee et al 2010), Etna (Ripepe et al 2018), Stromboli (Le Pichon et al 2021, Kilauea (Patrick et al 2019), and Sakurajima (Yokoo et al 2013).…”
Section: Eruption Monitoringmentioning
confidence: 99%
“…Incorporating topography can result in improved source localizations (Fig. 1; Fee et al 2021), and improved estimations of volumetric and mass flow rates (Kim et al 2015;.…”
Section: Infrasound Propagationmentioning
confidence: 99%
See 1 more Smart Citation
“…Reverse time migration (RTM) was proposed in the 1980s (Baysal, 1983;McMechan, 1983;Whitmore, 1983), which is based on a two-way wave equation and applies zero-lag crosscorrelation imaging conditions to realize imaging. Theoretically, RTM can adapt to any complex velocity model without dip limitations and image nearly all kinds of waves, including refractions, prismatic waves, diffractions, and multiples, so it is considered to be the most accurate imaging algorithm and has been widely used in the field data processing (Sun et al, 2015;Oh et al, 2018;Qu et al, 2020;Fee et al, 2021). However, due to using the two-way wave equation to implement wavefield continuation, the backward reflection will occur when the seismic wave propagates to the reflection interface.…”
Section: Introductionmentioning
confidence: 99%